In Vitro Shoot Regeneration From Nodal and Shoot Tip Explants of a Threatened Medicinal Plant - Smilax Zeylanica L. (Journal of Bio-Science, 2023)
An efficient protocol for in vitro clonal propagation of Smilax zeylanica was developed using nodal and shoot tip segments from field grown plants. Nodal explants performed better than shoot tip explants when two distinct explants were tested for shoot proliferation. The best results for shoot proliferation were achieved with MS medium supplemented with BAP and Kn alone or in combination with NAA and IBA at various concentrations. On MS medium containing 4.0 μM BAP, the greatest number of shoots were produced. In vitro proliferating shoots were transplanted to full strength MS medium fortified with IBA and NAA separately at varying concentrations (1.0 - 6.0 μM) in order to induce adventitious roots. The medium containing 2.0 μM IBA showed the best rooting reactions. Plantlets having well developed root system were transferred to soil and successfully acclimatized with 80% survival rate under ex vitro condition.J. Bio-Sci. 30(1): 69-78, 2022 (June)